Strong enhancement of cage effects in water photolysis caused by interatomic Coulombic decay - Jabbari, Ghazal; Sadri, Keyvan; Cederbaum, Lorenz S.; Gokhberg, Kirill (The journal of chemical physics, 2016)
The impact of the solvent on the photodissociation of embedded molecules has been intensively investigated in the last decades. Collisions of photofragments with the solvating atoms or molecules can change their kinetic energy distribution or even lead to the de-excitation of the dissociating molecule to a bound electronic state quenching the dissociation. In this article we show that this cage effect is strongly enhanced if interatomic Coulombic decay (ICD) of the excited state becomes allowed. Ab initio calculations in H2O-Cl− cluster show that the ultra-fast dissociation of water in the ÃÃ<mover accent="true">Ã</mover> excited state is strongly quenched by ICD. We found that this very efficient quenching is due to two factors. First, the lifetimes of the ÃÃ<mover accent="true">Ã</mover> state due to ICD are short ranging between 6 and 30 fs. Second, nuclear dynamics is dominated by the chattering motion of the H atom between O and Cl− allowing ICD to act for longer times. We hope that this work will be an important first step in clarifying the impact of ICD on photodissociation of embedded molecules.
Gesehen am 30.04.2020